Violent behaviour on construction sites: structural equation modelling of its impact on unsafe behaviour using partial least squares. Issue 10 (8th July 2020) - Adinyira, Emmanuel; Manu, Patrick; Agyekum, Kofi; Mahamadu, Abdul-Majeed; Olomolaiye, Paul Olaniyi
Abstract : Purpose: Work on construction sites involves individuals with diverse character, temperament, age, physical strength, culture, religion and experience level. A good number of these individuals are also alleged to involve themselves in substance and alcohol abuse due to the physically demanding nature of their work. These could promote the prevalence of violence on construction sites which could in turn affect safety on construction sites. However, there is a lack of empirical insight into the effect of violent behaviour and unsafe behaviour on construction sites. This study therefore pioneers an empirical inquiry into the relationship between violent behaviour and unsafe behaviour on construction sites. Design/methodology/approach: Seventeen violent behaviours and 15 unsafe behaviours were measured on 12 construction sites among 305 respondents using a structured questionnaire. A total of 207 valid questionnaire responses were collected from site workers. Partial least square–structural equation modelling (PLS-SEM) technique was used to examine the relationship between violent behaviour and unsafe behaviour. Findings: The results indicate that there is a significant positive relationship between violent behaviour and unsafe behaviour on construction sites. Originality/value: The findings from this study provide valuable insight into a less investigated dimension of the problem of construction site safety management. A focus on attitudinal issues such as how workers relate toward others and toward self should be an important consideration in safety improvement interventions on construction sites.